Country’s Research Priorities to the Research Initiative towards a Developed Research Agenda - Gian S. Maneja; John Ryel M. Galang; Jherimie P. Cayanan; Lee Anne Kyra M. Roman; Alma L. Tangcuangco; Armie C. Tolentino; Genesis C. Tiria (ASEAN Journal of Science and Engineering Education, 2023)
This study used a survey research design to determine the relevance of the country's research priorities based on the Commission on Higher Education (CHED), Department of Science and Technology (DOST), and The National Economic and Development Authority (NEDA), to the research initiatives of a Higher Education Institution (HEI) and Bachelor of Science in Electrical Engineering (BSEE) department. It employed random sampling of enrolled students, parents, alumni, and faculty to analyze discrepancies in the perceptions regarding the degree of applicability, significance, and urgency of the country's research priorities to the department's research initiatives. The focuses include several aspects related to CHED; Technology and education, indigenous renewable energy sources in the domestic energy, program/curricular studies on higher education, disaster risk management (multidisciplinary/multisector), and the national science and technology plan, among others, DOST. The country's research priorities need to be emphasized in the BSEE department's research agenda and initiatives, as these are all for the sake of achieving their institutional learning outcomes towards developing a skilled and competent workforce in the country's electrical engineering industry.